Annealed ZnO/Al2O3 Core-Shell Nanowire as a Platform to Capture RNA in Blood Plasma - Hiromi Takahashi; Takao Yasui; Annop Klamchuen; Narathon Khemasiri; Tuksadon Wuthikhun; Piyawan Paisrisarn; Keiko Shinjo; Yotaro Kitano; Kosuke Aoki; Atsushi Natsume; Sakon Rahong; Yoshinobu Baba (My University, 2021)
RNA analytical platforms gained extensive attention recently for RNA-based molecular analysis. However, the major challenge for analyzing RNAs is their low concentration in blood plasma samples, hindering the use of RNAs for diagnostics. Platforms that can enrich RNAs are essential to enhance molecular detection. Here, we developed the annealed ZnO/Al2O3 core-shell nanowire device as a platform to capture RNAs. We showed that the annealed ZnO/Al2O3 core-shell nanowire could capture RNAs with high efficiency compared to that of other circulating nucleic acids, including genomic DNA (gDNA) and cell-free DNA (cfDNA). Moreover, the nanowire was considered to be biocompatible with blood plasma samples due to the crystalline structure of the Al2O3 shell which serves as a protective layer to prevent nanowire degradation. Our developed device has the potential to be a platform for RNA-based extraction and detection.
Keywords: Advanced biosensing and bioanalysis techniques